Henry James and queer modernity - Haralson, Eric L (Cambridge University, 2013)
In Henry James and Queer Modernity, Eric Haralson examines far-reaching changes in gender politics and the emergence of modern male homosexuality as depicted in the writings of Henry James and three authors who were greatly influenced by him: Willa Cather, Gertrude Stein, and Ernest Hemingway.